CHANGING CONTOURS OF DISTRICT COLLECTOR IN LOCAL GOVERNANCE IN INDIA - Sole, Nagendra Ambedkar (European Scientific Journal, ESJ, 2014)
One of the notable contributions of the British to the Indian administration is the creation of the office of Collector and District Magistrate. Some eminent administrators of the past have described administrative apparatus that not only covers essential elements but also emphasizes that district administration comprising both regulatory and development as organic process. Thus the main thrust was in the unity of entire administration by covering various laws, rules and regulations under the general heading of the governance in India. It may be mentioned that law and order and development, which includes activities relating to social welfare form the main theme of district administration. On the whole, it also encompasses the nature and scope of good governance. Authors like Sastry and David Potter had emphasized some of these aspects in addition to the providing the historical provision, growth and development of district administration. Also, there is good amount of information on the district administration, in which District Collector and his supporting staffs plays an important role in collecting land revenue apart from attending the work related to the development, welfare and since 1959 by administering panchayati raj system. In this article an objective analysis is attempted on the changing contours of District Collector in local governance in India based on the relevant available literature.